Effect of hydrogenic impurity on linear and nonlinear optical absorption coefficients and refractive index changes in a quantum dot. (21st April 2015) - Guo, Kangxian; Zhang, Zhongmin; Mou, Sen; Xiao, Bo
Abstract: The analytical expressions of linear and nonlinear optical absorption coefficients and refractive index changes in a quantum dot with a hydrogenic impurity are obtained by using the compact-density-matrix approach and iterative method. The wave functions and the energy levels are obtained by using the variational method. Numerical results show that the optical absorption coefficients and refractive index changes are strongly affected by the hydrogenic impurity.